Nurses' role in the management of urinary incontinence in the elderly for the promotion of quality of life - Mendanha, Bárbara Dias; Mendes, Claudinea Farias Clementino; Silva, João Felipe Dias da; Figueira, Vívian Castilho; Menezes, Mariana Rodrigues da Silva de (Seven Editora, 2023)
Urinary incontinence is one of the most important syndromes of psychological and psychological quality, which interfere with the quality of life of the elderly, as they cause low self-esteem, limiting the individual's autonomy. Objective: To describe the role of nurses in the management of patients with urinary incontinence, promoting an improvement in the quality of life. Method:  It’s about a literature review, integrative type, composed of 09 studies, whose data collection was carried out through the following data base: Base de Dados de Enfermagem (BDENF), Índice Bibliográfico Español en Ciencias de la Salud (IBECS), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Biblioteca Regional de Medicina (MEDLINE) and U.S. National Library of Medicine (PUBMED). Results: The importance of training nursing professionals in care, planning and interventions aimed at the elderly affected by UI is highlighted, in which the management of the geriatric syndrome is stimulated. Final considerations: It is noted the importance of the nurse's role as an agent to promote quality of life in geriatric patients affected by urinary incontinence. DOI:https://doi.org/10.56238/ptoketheeducati-062